STUDY OF COMBINING ABILITY AND HETEROSIS FOR SEED YIELD AND SEED QUALITY TRAITS IN RAPESEED [BRASSICA RAPA L.] - N. H. CHAUDHARI; R. N. PATEL; R. A. GAMI; S. K. SHAH (The Bioscan, 2015)
Combining ability, gene action and heterosis was studied in a set of nine parents, their 36 hybrids and one standard check (Benoy) of rapeseed following half diallel analysis. The ratio of ó 2 gca / ó 2 sca suggested predominance of non- additive gene effects for all the characters except days to maturity. Based on general combining ability effects the parents GS 1 and PS 66 were good general combiners for seed yield per plant and component traits. While parents SPAN, AA 14 and SSK 9203 proved to be good general combiners for quality traits viz., oil content (%), erucic acid (%). The cross combinations NDYS 53-1 x AA 14 ,YSB 2001 x SSK 9203 and SPAN x SSK 9203 exhibited significant sca effects for seed yield per plant and its associated traits. The promising crosses based on standard heterosis were PS 66 x YSB 2001, GS 1 x YSB 2001 and GS 1 x YSB 4-2005. The hybrids PS 66 x NDYS 53-1 and SSK 9203 x AA14 were found promising based on high sca and heterosis for oil content and erucic acid.